KOMPOSISI DAN STRUKTUR KOMUNITAS ZOOPLAKTON DI DANAU TALAGA, SULAWESI TENGAH - Melisa Melisa; Asri Pirade Paserang (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Study of composition and community structure of zooplankton in Talaga Lake was conducted from February to March 2019. The aimed of this research was to know the composition and structure of zooplankton in Talaga lake, Central Sulawesi. Samples were collected at four station by using purposive sampling method. The identification results have found 4 genus of zooplankton with each composition 71 % of Cyclops, 22 % of Daphnia, 0,34 % of Paramecium and 6,64 % of Chaoborus. The zooplankton abundance is around 11.6-17.2 ind/l. Community structure of zooplankton in Talaga Lake is unstable which shows by the low value of diversity index (0.68 to 0.8) and uniformity index (0,49-0,57). The value of dominance index which is in range 0.51-0.58 has also shown that there is dominant type of zooplankton.